Evaluation of the Radioactivity of Cement and Raw Materials used in its Manufacture in the Kirkuk Cement Company - Alaa Fadhil Hashim; Omar Mahmood Murbat(; Zaki Abdul Jabbar; Ali Hussein obaid; Munir Anwar bakir (Journal of Madenat Alelem University College, 2020)
This research was conducted to evaluate the radiation activity of cement and raw materials used in the Kirkuk cement plant by taking samples of cement production stages. The qualitative radiation activity of Ra226, Thorium Th232 and Potassium K40 were measured. The concentration of the gamma spectrometry(HPGE) using the sophisticated Genie 2000 software. The concentration of isotopes was as follows: (0.16 ± 0.88 ± 0.73) Bq / Kg for Ra226, (4.88 ± 0.72 - 53.48 ± 6.49) Bq / Kg for Th232, (128.20 ± 9.18 - 289.55 ± 12.15) Bq / Kg for K40 The Raeq, I gamma, Hex, Hin, indoor D intake and Iα in cement samples and raw materials to assess potential radiological risks to human health were also calculated to determine the radioactivity content of the buildings and radiological hazards associated with these buildings. The results of the research presented showed that the concentration of the specific radiological activity of Ra226, Th332 and K40 thorium was the concentration of radioisotopes in the resulting cement and raw materials within the permissible range according to scientific recommendations of UNSCEAR 1 and radiation indicators such as Raeq All samples are in the range of globally determined values. The average of Raeq values ​​for the measured samples from Bq / kg (117 - 31), which is below the internationally permissible values ​​(370 Bq kg-1), the I gamma index is less than 1, Of 1 and the dose rate absorbed in indoor air intake Alpha index is relatively Iα less than 1. The study shows that cement is not a dangerous source of radiation and is safe for use in housing construction. When compared with concentrations of cement in some countries, it is found to be less or close to the radiation activity of those countries. By observing the concentration of radionuclides in the raw materials, additives and final output, most radionuclides are released with alkali materials, which are an accidental product, disposed of as waste.